Sistema de facturación electrónica en el Comercial David & David en el año 2021. - Cedeño Tinoco, Morelia Isabel (2022)
Commercial David began its commercial activities on November 29, 2012 with RUC number 1203745052001, under the name of Elinan Moreira Olga Janet located in the Province of Los Ríos, Montalvo canton. The problem in this case lies in the great lack of training and updating of knowledge regarding the issuance of electronic documents. The Commercial does not have knowledge of how to implement electronic invoicing correctly, they also do not know which are the certified entities for the issuance of electronic signatures in Ecuador, expressing great uncertainty in Commercial David, since the rules and ordinances of the SRI vary. The line of research will be through the subline of financial, tax and social commitment management, the objective is to carry out the implementation of electronic invoicing in this establishment, making known the steps to follow. The present case study "electronic invoicing system in the commercial David & David in the year 2021", which according to its modality corresponds to a development project, insofar as it intends to solve real problems through the evaluation of the project in matter of this, it was carried out under the qualitative methodology. The owner of the company expects good results and that these will be benefits for clients and collaborators to achieve their proposed objectives through the application of a complete agile and efficient process so that it does not generate complications for both parties in the future.